Perancangan Sistem Digitalisasi Arsip (E-Arsip) Dengan Metode Prototype Berbasis Web Menggunakan Framework Codeigniter 4 - Andri Geo (CV. Multi Kreasi Media, 2023)
Management and governance of archives is a must for government agencies in an effort to create good government. Archives as evidence that is actual and can be accounted for because the archive is part of the source of information, recording activities or events of the implementation of activities, related to the archives stored must be well organized and managed with proper maintenance and storage so that the existence of archives can be maintained within a certain period of time. Adapting to the times, archive storage facilities in physical form are slowly turning into archive digitization systems (e-archives) so that archive storage, search and security are more effective and efficient.